CRISPR-Cas9, the new kid on the block of fungal molecular biology - Krappmann, Sven (Medical Mycology, 2017)
Research on fungal pathogens with the aim to identify virulence determinants strictly relies on the generation of defined, recombinant strains, a task that is executed by means of a sophisticated molecular biology toolbox. Recent developments in fungal genome engineering have opened a new frontier by implementing the CRISPR-Cas9 technology, based on expression of the Cas9 endonuclease that is loaded by a single guiding RNA (sgRNA) molecule to target a defined site in the recipient genome. This novel approach has been adapted successfully to engineer fungal genomes, among them the one of the human-pathogenic mould Aspergillus fumigatus Implementation of the required components was achieved by various means that differ with respect to expression of the Cas9 enzyme and sgRNA delivery. Validation of CRISPR-Cas9-mediated mutagenesis could be executed by targeting selected candidate genes of A. fumigatus to provide a promising perspective for screening and multiplexing approaches to scrutinize the virulome of this opportunistic fungal pathogen in a comprehensive manner, such as by analyzing genetic polymorphisms or the function of gene families.
EVALuna2:7747